Characteristics of the Short Distance Transported Fluvial Sediments in an Arid Environment - Joshi, D C; Sharma, K D (Annals of Arid Zone, 2016)
Characteristics of the short distance transported sediments in an arid environment have been studied. Sediment derived from the sandy plain, dune complex and rocky gravelly catchments contained more clay and silt than the matrix soil. The sand fraction of these sediments, dominated by poorly sorted finer grade, showed narrower size range than the soil proper indicating restricted velocity fluctuation during sedimentation.